Dorsal root ganglia in Friedreich ataxia: satellite cell proliferation and inflammation - Koeppen, Arnulf H. (Acta Neuropathol Commun, 2016)
INTRODUCTION: Dorsal root ganglia (DRG) are highly vulnerable to frataxin deficiency in Friedreich ataxia (FA), an autosomal recessive disease due to pathogenic homozygous guanine-adenine-adenine trinucleotide repeat expansions in intron 1 of the FXN gene (chromosome 9q21.11). An immunohistochemical and immunofluorescence study of DRG in 15 FA cases and 12 controls revealed that FA causes major primary changes in satellite cells and inflammatory destruction of neurons. A panel of antibodies was used to reveal the cytoplasm of satellite cells (glutamine synthetase, S100, metabotropic glutamate receptors 2/3, excitatory amino acid transporter 1, ATP-sensitive inward rectifier potassium channel 10, and cytosolic ferritin), gap junctions (connexin 43), basement membranes (laminin), mitochondria (ATP synthase subunit beta and frataxin), and monocytes (CD68 and IBA1). RESULTS: Reaction product of the cytoplasmic markers and laminin confirmed proliferation of satellite cells and processes into multiple perineuronal layers and residual nodules. The formation of connexin 43-reactive gap junctions between satellite cells was strongly upregulated. Proliferating satellite cells in FA displayed many more frataxin- and ATP5B-reactive mitochondria than normal. Monocytes entered into the satellite cell layer, appeared to penetrate neuronal plasma membranes, and infiltrated residual nodules. Satellite cells and IBA1-reactive monocytes displayed upregulated ferritin biosynthesis, which was most likely due to leakage of iron from dying neurons. CONCLUSIONS: We conclude that FA differentially affects the key cellular elements of DRG, and postulate that the disease causes loss of bidirectional trophic support between satellite cells and neurons.